Capital Structure, Growth Opportunity, and Firm Value: Dynamic Insights from the Indonesian Food and Beverage Industry - Dani Lismanto (CV. Era Digital Nusantara, 2026)
This study examines how capital structure and growth opportunities affected the firm value of Food and Beverage (F&B) companies on the Indonesia Stock Exchange during the volatile 2019–2023 period. While the COVID-19 pandemic disrupted consumer markets, the strategic balance between debt financing and growth potential in maintaining market confidence remains underexplored. Using a causal quantitative approach with purposive sampling, this study analyzed 25 firm-year observations from 5 consistently active companies using Multiple Linear Regression. The empirical results indicate that capital structure has a positive and significant effect on firm value, whereas growth opportunities do not have a significant effect on firm value. Simultaneously, both variables explain 34.6% of the variance in firm value. These findings imply that during economic crises, investors prioritize robust corporate financing strategies over long-term expansion projects. Consequently, F&B managers should focus on optimizing debt-to-equity ratios rather than aggressive scaling to maintain market confidence and protect investor returns during volatile periods.